Is health literacy clue on the self-efficacy of diabetes patients? (Annals of Medical Research, 2022)
Aim: This research was conducted to evaluate the relationship between health literacy level and self-efficacy in patients with diabetes mellitus.Materials and Methods: This cross-sectional study was conducted inpatient and outpatient clinic of internal medicine at the city hospital. The sample of the study consisted of 700 conscious patients diagnosed with diabetes mellitus for at least one year. The data of the study were collected using the Health Literacy Questionnaire-European Union Scale and Type 2 Diabetes Self-Efficacy Scale. Data were analyzed using regression analysis and correlation analyses.Results: In this study, the level of health literacy general index was sufficient level, and the average of the self-efficacy scale was high. It was observed that health promotion and health service literacy level were effective in estimating the self-efficacy level of diabetes patients. As the health literacy level of patients for health service and health promotion increased, general self-efficacy level increased.Conclusion: Health promotion and health service literacy level are effective in estimating the self-efficacy level of diabetes patients.
Keywords: Diabetes mellitus; Health literacy; Self-efficacy level